A real-time adaptive look-ahead speed control algorithm for FDM-based additive manufacturing technology with Hbot kinematic system. Issue 6 (22nd July 2019) - Qin, Qin; Huang, Jigang; Yao, Jin
Abstract : Purpose: The purpose of this paper is to enhance the accuracy as well as efficiency of high-speed machining, avoid the speed fluctuation caused by acceleration/deceleration (ACC/DEC) and increase the smoothness of feedrate in continuous corners or curves machining. The Hbot kinematic system was analyzed and combined with fused deposition modeling-based (FDM) additive manufacturing (AM) technology. Then a real-time adaptive look-ahead speed control algorithm was proposed. Design/methodology/approach: To validate the performance of Hbot kinematic system and the proposed speed control algorithm, the positioning accuracy of Hbot and cross structure was compared. Also, the experimental verification was conducted among FDM based 3-D printer with cross structure as well as open source speed control algorithm (FDM with cross-OS), cross structure and the proposed speed control algorithm (FDM with cross-PS) and Hbot structure, as well as the proposed speed control algorithm (FDM with Hbot-PS), respectively. Findings: The results indicate that the Hbot kinematic system leads to the high stability of positioning accuracy due to the small motion inertia. Furthermore, the experimental verification shows that the efficiency, printing precision and surface finish of models for FDM with Hbot-PS are obviously higher than that for FDM with cross-PS as well as FDM with cross-OS, while FDM with cross-OS shows the worst performance. The contribution of Hbot kinematic system and the proposed speed control algorithm to FDM based AM technology was validated by this work. Practical implications: The Hbot kinematic system and proposed speed control algorithm have the important implication of improving the accuracy of FDM machines, especially in the low-price range segment. Also, this work can help future system developers show a possible way of tackling the motion inertia problem. Originality/value: The study of Hbot kinematic system and proposed algorithm are expected to advise the current research for improving the accuracy as well as the efficiency of FDM-based AM technology.